Intra-Personal Compromises - Räikkä, Juha (Italian Society for Analytic Philosophy (SIFA), 2025)
The most usual philosophical questions about compromises have been those related to inter-personal compromises, in which parties are compromising with each other, rather than intra-personal compromises, which are often psychologically demanding. This paper aims to fill the gap in the discussion and briefly analyze the nature of intra-personal compromises. The starting point here is the assumption that inter-personal compromises cannot be made without intra-personal compromises, although intra-personal compromises are common even when they are not linked to inter-personal compromises. The main question addressed in the paper is whether the intra-personal compromises that we accept in all kinds of contexts are similar to those intra-personal compromises that we make when we compromise with others. I argue that they are more or less similar, although there are also some distinctive features in intra-personal compromises that are involved in inter-personal compromises. When a person makes an intra-personal compromise in the context of an inter-personal compromise she is forced to act under uncertainty, as she cannot know beforehand what options are really available. The price of the compromise is known only after the negotiation process. This is a special feature, or so I will claim